Pengembangan Media Buku Dongeng Digital untuk Keterampilan Menyimak Siswa Kelas III di SDN Cilenggang 02 - Nadia Arta Dewi; Ujang Jamaludin; M. Taufik; Rina Yuliana (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2022)
AbstrackThis study discusses the development of digital tales book media for scrutinize skills of third grade elementary school students. This study aims to produce a digital tales book media product that contains fairy tales in Indonesian lessons. This media was created to help support learning for teachers and students. This research was conducted using the Research and Development (R&D) method using the ADDIE model which consists of five stages, namely: Analysis, Design, Development, Implementation, Evaluation. It can be concluded that the feasibility of a digital fairy tale book product for listening skills is obtained from the results of an assessment by experts, namely media experts, material experts, and linguists. The results of the assessment of media experts were 89%, material experts 97%, and linguists 95.6%. So it can be concluded that the results of the assessment given by the experts obtained the